Mechanical Properties of Recycled Polymer Materials in Additive Manufacturing - Pernica, Jakub; Vodak, Matej; Sarocky, Robert; Sustr, Michal; Dostal, Petr; Cerny, Michal; Dobrocky, David (Manufacturing Technology Journal, 2022)
The publication focuses on the testing of the tensile strength of samples produced by Fused Filament Fabrication additive manufacturing technology. Three materials rPLA, rPETG and rPET were tested. These materials are recycled PLA (Polylactic Acid), PETG (Polyethylene Terephthalate Glucol) and PET (Polyethylene Terephthalate). These materials were used to create samples for tensile testing according to ASTM D638. In addition to testing the materials, the methodology was also tested using sets of specimens printed with no outer perimeters, one outer perimeter and two outer perimeters. Tensile diagrams were created from the measured data. Statistical processing and comparison of the measured data is performed in the publication. In the discussion, a comparison of the mechanical properties of recycled materials for 3D printing versus virgin materials for 3D printing by Fused Filament Fabrication technology is made.
Keywords: Additive Manufacturing; Polymer Materials; ASTM D638; Recycled Materials; Material Properties